Number and nature of psychiatric emergency department visits in a tertiary hospital before, during, and after coronavirus pandemic - Aymerich, Claudia; Pedruzo, Borja; Salazar de Pablo, Gonzalo; Olazabal, Nora; Catalan, Ana; González-Torres, Miguel Ángel (Frontiers in Psychiatry, 2024)
The COVID-19 pandemic has significantly impacted mental health globally, leading to a deterioration in the overall mental health of the population and changes across all healthcare levels, including emergency departments (ED). However, the evolution of the quantity and nature of psychiatric ED visits in the post-pandemic period remains uncertain.Aims: To examine changes in the number and nature of psychiatric emergencies at a general hospital before, during, and after the COVID-19 pandemic.Psychiatric ED visits from a tertiary hospital in the Basque Country (Spain) between January 2019 and November 2023 were investigated. Electronical health registers detailing the number and nature of psychiatric care consultations were analyzed for the study timeframe. Three periods were then compared: pre-pandemic (from January 2019 to February 2020), pandemic (from March 2020 to January 2022), and post-pandemic (from February 2022 onwards).Results: 16,969 psychiatric ED visits were recorded for the study period. The number of psychiatric ED visits remained stable from pre-pandemic (269.93 visits/month) to pandemic (264.48 visits/month) periods but experienced a significant rise during the post-pandemic period (330.00 visits/month; t=-6.42; p<0.001), which was not reflected in medical and traumatological visits. The proportion of visits for anxiety (Z=-2.97; p=0.003), suicidal ideation (Z=-5.48; p<0.001), and administrative and social consultations (Z=-5.69; p<0.001) increased over the course of the pandemic. In contrast, visits for schizophrenia and other psychotic disorders (Z=4.85; p<0.001), as well as unspecified behavioural alterations (Z=2.51; p=0.012), significantly decreased.The COVID-19 pandemic and its aftermath have altered the patterns of urgent psychiatric care, characterized by a sharp increase of average monthly number of consultations and a shift in their nature. Future efforts should focus on characterizing this surge in demand and enhancing both emergency services and outpatient settings.